An overview of traditional Chinese medicine therapy for Helicobacter pylori–related gastritis. Issue 3 (25th March 2021) - Li, Yuli; Li, Xiaoya; Tan, Zhoujin
Abstract: Background: Helicobacter pylori –associated gastritis (HPAG) is a common digestive system disease that its therapeutic goal is to eradicate Helicobacter pylori . However, due to the widespread use of antibiotics, problems for example, antibiotic resistance, reinfection, and gastrointestinal side effects have emerged. The solution of above problems provides a broad space for traditional Chinese medicine (TCM) to exert its remarkable advantages on the treatment of HPAG. Methods: Extensive database retrieval using platforms not limited to but including Web of Science, SpringerLink, ScienceDirect, Google Scholar, China National Knowledge Infrastructure, Wanfang, and VIP database was performed using keywords such as " Helicobacter pylori ‐associated gastritis" or "HPAG" or " Helicobacter pylori " or " H . pylori " or "gastritis" and "traditional Chinese medicine" or "TCM" or "herbs" or "Chinese herbal medicine". In addition, related books, PhD, and master's dissertations were also researched to provide a comprehensive review. Results: This review mainly introduces the clinical efficacy of TCM formulas for HPAG, as well as active ingredient and pharmacological mechanisms of herbs. What's more, this review puts forward potential prospects for future research. Conclusion: These research works have shown the therapeutic benefits of TCM in the treatment of HPAG. The development of TCM with more specific functions and practical data will not only become a significant trend in the world market but also have an irreplaceable role in the future treatment of HPAG. More continued researches should be undertaken in the future.